Analisa Rasio Kemandirian Daerah dan Rasio Keuangan Terhadap Kinerja Keuangan Pemerintah Daerah - Melina Febi Awani; Swarmilah Hariani (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2021)
This study aims to analyze the performance of local governments in all districts on the island of Sumatra for the 2015-2018 budget year. The data used is secondary data obtained from the Audit Board of the Republic of Indonesia in the form of a Budget Realization Report for the 2015-2018 fiscal year. This study is a descriptive study using an analysis of regional independence ratios and financial ratios to assess the performance of local governments in all districts on the island of Sumatra. The results showed that, the development of the level of regional independence of all districts on the island of Sumatra during 2015-2018 was at a low point, namely with an average yield of only 25%, so for the development of the level of efficiency in the management of regional expenditures of all districts on the island of Sumatra, it can be said less efficient. And then for the development of the level of effectiveness of the management of Regional Original Income, it can be said to be effective, namely with an average yield of above 90%, while for the growth rate of Regional Original Income it is still in a fluctuating condition.